2014
DOI: 10.1007/s00268-014-2596-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgical Margins on the Outcome of Breast Cancer Patients: A Retrospective Analysis

Abstract: We found the status of resection margins and the management of infiltrated or narrow margins to have no significant influence on local tumor recurrence rates or on overall patient survival. Instead, biological factors connected with tumor aggressiveness seem to play the most important role in breast cancer prognosis, independent of surgical radicality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…DCIS grows along the ducts in the breast without invasion of the underlying tissue, which results in a non-palpable lesion difficult to remove with tumor-free margins. When EDCIs are completely removed with negative tumor margins, it loses its predicative value for LRR [ 5 , 14 19 ]. In a pooled analysis of the EORTC 10801 and the DBCG 82 TM trials, lympho-vascular invasion causes a higher risk of LRR after BCT [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCIS grows along the ducts in the breast without invasion of the underlying tissue, which results in a non-palpable lesion difficult to remove with tumor-free margins. When EDCIs are completely removed with negative tumor margins, it loses its predicative value for LRR [ 5 , 14 19 ]. In a pooled analysis of the EORTC 10801 and the DBCG 82 TM trials, lympho-vascular invasion causes a higher risk of LRR after BCT [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the present review, an updated literature search replicating that from Houssami et al [10, 12•] was performed in December 2015 to assess whether studies published subsequent to reports of the margins meta-analysis [ [38,39] have shown findings that are consistent with the conclusions of the margin metaanalysis [12•]. However, a study conducted in Australia based on 2300 patients with invasive BC reported that a positive margin or a margin of 1 mm (for margins obtained at BCS or mastectomy) had an increased risk of LR (HR 2.72; 95 % CI 1.30-5.69), whilst margins of 2 mm or wider were not associated with increased risk of LR; on that basis, the study from Behm et al recommended a 2-mm width for negative margins [40].…”
Section: Is There New Evidence To Contradict a Recommendation For A Mmentioning
confidence: 99%
“…The specimen is then oriented with some stitched in order to facilitate the margin evaluation by the pathologist [83]. In particular, a negative margin greater than 2 mm represents nowadays the adequate margin for DCIS [84].…”
Section: Conservative Breast Surgerymentioning
confidence: 99%